Maoist and naxalite politics in India - "Das, S" (New Delhi, 2011)
This book is an attempt to provide sources and first hand reports to our readers in order to understand this complex problem of Maoists and Naxalite Politics in India. Who are Maoists and Naxalites What is their origin? How they plan and organize This book makes available the documents from which readers can find answers to some of the questions on Politics of Maoists and Naxalites Politics in India. While preparing this work, we have incurred indebtedness of the authorities and activists-reports on the subject.
Keywords: Naxalism-Politics-India